Angiogenic and vascular analysis: a comparative study between healthy and tumoral breast adipose stroma - Pagnotta, Priscila Ayelén (2024)
Angiogenesis is essential for growth, development, wound healing, and plays a pivotal role in diseases, including cancer. In breast cancer, the microenvironment, mainly adipose tissue, contributes to the progression, may promote angiogenesis.